Pasar Tradisional Versus Pasar Modern di Daerah Perkotaan (Studi Kasus: Kecamatan Gondokusuman Kota Yogyakarta) - Sadino, Sadino; Syahbana, Joesron Alie (Magister Pembangunan Wilayah dan Kota,Undip, 2014)
This study aims to determine how the competition is going on between the traditional versus the modern market in urban areas include aspects of characteristics, range of services, as well as the preferences of consumers' perceptions of the two types of markets. The method used is a quantitative method. The sampling technique used is non probabilitiy type of purposive sampling for market population and type of accidental sampling technique for the consumer population. The results showed that from the aspect of phisical condition characteristic, the traditional market is still less than the modern market. From the aspect of outreach, the modern market has a wider service area. Consumer shopping preferences to traditional markets are still higher than in the modern market. Cross-tabulation analysis showed a significant relationship between the variables of age and education ranges by selecting the type of retail (traditional or modern). Consumer perception analysis showed the superiority of the modern market than traditional market in the attributes of diversity, quality, convenience, promotion and location.